Norepinephrine regulates cocaine-primed reinstatement via α1-adrenergic receptors in the medial prefrontal cortex. (June 2017) - Schmidt, Karl T.; Schroeder, Jason P.; Foster, Stephanie L.; Squires, Katherine; Smith, Brilee M.; Pitts, Elizabeth G.; Epstein, Michael P.; Weinshenker, David
Abstract: Drug-primed reinstatement of cocaine seeking in rats is thought to reflect relapse-like behavior and is mediated by the integration of signals from mesocorticolimbic dopaminergic projections and corticostriatal glutamatergic innervation. Cocaine-primed reinstatement can also be attenuated by systemic administration of dopamine β-hydroxylase (DBH) inhibitors, which prevent norepinephrine (NE) synthesis, or by α1-adrenergic receptor (α1AR) antagonists, indicating functional modulation by the noradrenergic system. In the present study, we sought to further discern the role of NE in cocaine-seeking behavior by determining whether α1AR activation can induce reinstatement on its own or is sufficient to permit cocaine-primed reinstatement in the absence of all other AR signaling, and identifying the neuroanatomical substrate within the mesocorticolimbic reward system harboring the critical α1ARs. We found that while intracerebroventricular infusion of the α1AR agonist phenylephrine did not induce reinstatement on its own, it did overcome the blockade of cocaine-primed reinstatement by the DBH inhibitor nepicastat. Furthermore, administration of the α1AR antagonist terazosin in the medial prefrontal cortex (mPFC), but not the ventral tegmental area (VTA) or nucleus accumbens (NAc) shell, attenuated cocaine-primed reinstatement. Combined, these data indicate that α1AR activation in the mPFC is required for cocaine-primed reinstatement, and suggest that α1AR antagonists merit further investigation as pharmacotherapies for cocaine dependence. Highlights: Inhibition of NE synthesis blocks cocaine-primed reinstatement. α1AR activation restores cocaine-primed reinstatement to NE-depleted animals. Blockade of α1ARs in the mPFC attenuates cocaine-primed reinstatement. Blockade of α1ARs in the VTA or NAc has no effect on cocaine-primed reinstatement.